Uterine leiomyomas with inclusion bodies: an immunohistochemical and ultrastructural analysis of 12 cases - Dundr, Pavel; Povýšil, Ctibor; Tvrdík, Daniel; Mára, Michal (Pathology, research and practice, 2007)
We describe 12 cases of leiomyoma with intracytoplasmic inclusion bodies, which were detected in a group of 447 leiomyomas examined at our institution between December 2005 and March 2006. Ten of these tumors were typical leiomyomas, and two cases represented atypical (bizarre) leiomyoma. In some cases, the presence of intracytoplasmic inclusion bodies resulted in a rhabdoid or skeletal muscle-like appearance of the tumor cells. Ultrastructurally, there were two types of inclusions. One of them consisted of an abnormal aggregation of intermediate and actin filaments. Another type of inclusions was composed of dense granular material without an apparent fibrillar structure. The ultrastructure of the inclusions correlates with immunohistochemical and histochemical stainings. The inclusions with apparent fibrillar arrangements were PAS negative, stained red by trichrome, and were, at least at the periphery, actin-, desmin-, and h-caldesmon-positive. The dense granular inclusions were at least focally PAS-positive, stained red by trichrome, and were negative immunohistochemically. The intracytoplasmic inclusions were found in atypical (bizarre) leiomyomas of the uterus and occasionally in epithelioid leiomyomas and leiomyosarcomas. However, to the best of our knowledge, these inclusions have not been found in typical uterine leiomyomas to date.
Keywords: financování organizované; dospělí; Calmodulin-Binding Proteins; diferenciální diagnóza; Female; biologické markery; Biomarkers; Keratins; Adult; ženské pohlaví; Periodic Acid-Schiff Reaction; azosloučeniny; Eosine Yellowish-(YS); Immunohistochemistry; lidé; vimentin; Rhabdoid Tumor; Uterine Neoplasms; keratiny; methylová zeleň; buněčná inkluze; Vimentin; rhabdoidní nádor; Methyl Green; imunohistochemie; Diagnosis, Differential; Financing, Organized; Inclusion Bodies; Azo Compounds; nádory dělohy; desmin; aktiny; Actins; Aged; Leiomyoma; eosin; Desmin; myogenin; Schiffova reakce; lidé středního věku; senioři; leiomyom; MyoD Protein; Middle Aged; proteiny vázající kalmodulin; Myogenin; Humans